A herança estruturalista de Durkheim nas ciências sociais - Gabriel E. Silveira; Yago Quiñonez Triana (Ciências Sociais Unisinos)
The article discusses the assimilation of some aspects of Durkheims structuralism by Bourdieu and Lévi-Strauss. In Durkheims view, the fundamental categories of human thinking are socially built, due to the ontological priority of the collective. These categories seem to be structured in opposing pairs. Bourdieu admits that this type of categories is at the basis of the construction of the social space and habitus, even in contemporary societies. Although Lévi-Strauss disagrees with Durkheim in terms of problems and hypotheses, he is in accordance with him on the assumptions of structuralism. He admits, for instance, that the totemic structure of opposing pairs is a universal category.